Outcome of Patients with Metabolic-Associated Fatty Liver Disease Who Are Infected with SARS-CoV-2: A Meta-Analysis - Chyntia Olivia Maurine Jasirwan; Dyah Purnamasari; Alvina Widhani; Tasya Kamila (Acta Medica Indonesiana, 2025)
Background: Metabolic-associated fatty liver disease (MAFLD) is excess fat accumulation in the liver due to metabolic syndrome. Coronavirus disease 2019 (COVID-19) is an infection caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 not only attacks the respiratory system but also involves systemic and extra-pulmonary organ disorders, including liver disorders. This review evaluates the severity of COVID-19, mortality, and length of hospital stays of patients with MAFLD who were infected with SARS-CoV-2. Methods: Literature searches were conducted through various online databases. The risk of bias assessment was conducted by two researchers using the Newcastle Ottawa Scale tool for NRSI studies, and any discrepancies were resolved by another team member. The meta-analysis was performed using Revman 5.4.1 and results were presented in forest plot by calculating the pooled odds ratio or mean difference between the MAFLD and non-MAFLD groups from the evaluated studies with a 95% CI. Results: The results of the meta-analysis using a fixed-effect model from seven studies showed that COVID-19 patients with MAFLD were associated with a higher mortality compared to those without MAFLD (OR 1.41, 95% CI 1.19-1.69, p=0.01, I2 48). However, there were no differences in COVID-19 severity (OR 3.12, IK95% 0.89–11.03, p=0.08, I2 92) and length of hospital stay (MD 1.27, CI95% 0.03–2.52, p=0.04, I2 80) between the two groups. Conclusion: MAFLD patients infected with SARS-CoV-2 were associated with higher mortality than non-MAFLD patients, but they were not associated with greater severity of COVID-19 nor a longer duration of hospitalization.